2016
DOI: 10.1080/15622975.2016.1224926
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5-hydroxytryptamine receptor gene polymorphisms modulating hyperprolactinaemia in antipsychotic drug-treated patients with schizophrenia

Abstract: Objectives: Hyperprolactinaemia (HPRL) is a classical side effect of antipsychotic drugs primarily attributed to blockade of dopamine D2 subtype receptors in the pituitary gland. Although dopamine is considered the primary factor inhibiting prolactin release, the activity of prolactin-producing lactotrophs is also regulated by the secretagogues thyrotrophin releasing hormone, vasoactive intestinal polypeptide and serotonin (5-hydroxytryptamine; 5-HT). Methods: We describe the association between HPRL and a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
23
1
1
Order By: Relevance
“…In a previous study, none of the studied HTR2A and HTR2C polymorphisms were associated with antipsychotic‐induced hyperprolactinaemia. However, a tendency of association was found between HTR2C rs3813929 and prolactin levels when treated with several antipsychotic drugs . In the current study, volunteers carrying the HTR2C rs3813929 C/C genotype had significantly lower prolactin AUC 0‐12 and C max levels than T allele carriers, suggesting a lower HTR2C occupancy than individuals carrying the T allele.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…In a previous study, none of the studied HTR2A and HTR2C polymorphisms were associated with antipsychotic‐induced hyperprolactinaemia. However, a tendency of association was found between HTR2C rs3813929 and prolactin levels when treated with several antipsychotic drugs . In the current study, volunteers carrying the HTR2C rs3813929 C/C genotype had significantly lower prolactin AUC 0‐12 and C max levels than T allele carriers, suggesting a lower HTR2C occupancy than individuals carrying the T allele.…”
Section: Discussioncontrasting
confidence: 47%
“…HTR2A and HTR2C polymorphisms were analysed related to hyperprolactinaemia in schizophrenic patients treated with classical and/or atypical antipsychotic drugs in a previous study: they found no association between HTR2A polymorphisms and hyperprolactinaemia. However, a significant association was established in case of various HTR2C polymorphisms . Nevertheless, prolactin concentrations in schizophrenic patients after ARI administration were not affected by DRD2 rs1800497, rs6277 polymorphisms and CYP2D6 phenotype …”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations